The new Blackwell companion to the sociology of religion - Turner, Bryan S. (Malden, MA : Wiley-Blackwell, 2010)
Reflecting the latest developments in the field, this book provides a comprehensive introduction to the sociology of religion with a clear emphasis on comparative and historical approaches. It covers major debates in secularization theory, rational choice theory, feminism, and the body.
Includes bibliographical references and index.
Keywords: Religion and sociology